Numerical Simulation of Turbulent Fluid Flow and Heat Transfer in a Ribbed Rotating Two-Pass Square Duct - Tong-Miin Liou; Shih-Hui Chen; Yi-Chen Li (International Journal of Rotating Machinery)
The local turbulent fluid flow and heat transfer in a rotating two-pass square duct with 19 pairs of in-line 90∘ ribs have been investigated computationally. A Reynolds-averaged Navier-Stokes equation (RANS) with a two-layer k−ε turbulence model was solved. The in-line 90∘ ribs were arranged on the leading and trailing walls with rib height-to-hydraulic diameter ratio and pitch-to-height ratio of 0.136 and 10, respectively. The Reynolds number, based on duct hydraulic diameter and bulk mean velocity, was fixed at 1.0×104 whereas the rotational number varied from 0 to 0.2. Results are validated with previous measured velocity field and heat transfer coefficient distributions. The validation shows that the effect of rotation on the passage-averaged Nusselt number ratio can be predicted reasonably well; nevertheless, the transverse mean velocity and, in turn, the distribution of regional-averaged Nusselt number ratio are markedly underpredicted in the regions toward which the Coriolis force is directed. Further CFD studies are needed.